Are Visitors Dangerous Carriers of Pathogens in The Hospital? an Observational Study in an University Hospital in Sicily. Issue 3 (3rd July 2019) - Ragusa, Rosalia; Giorgianni, Gabriele; Faro, Giuseppina; Lazzara, Antonio; Bellia, Maria Alessandra; Marranzano, Marina
Abstract: The hospital environment has been suggested as having an important role in the transmission of health care-associated infections. The aim of this work is to clarify the possible role of visitors in environmental contamination at our hospital. The microbial load was determined by Rodac plate contact on flat surfaces and by swabs on uneven surfaces. A total of 137 samples were taken from four different areas of the hospital unit. The results were divided into two groups according to the types of subjects that most often frequented those environments. We found that the transmission of health care-associated infections (HAIs) occurs mainly in areas where visitors are not allowed.